2021
DOI: 10.3347/kjp.2021.59.4.369
|View full text |Cite
|
Sign up to set email alerts
|

Human Taeniasis and Cysticercosis and Related Factors in Phu Tho Province, Northern Vietnam

Abstract: Several factors presumed to facilitate the transmission of Taenia spp. were reported in Vietnam. We conducted a cross-sectional study taking questionnaires from 1,185 participants, and collecting 1,151 sera and 1,036 stool samples in northern Vietnam. Sera were examined for circulating antigens of Taenia solium cysticerci using ELISA, stools for Taenia eggs by Kato-Katz smear, and copro-antigens by ELISA. Ag-ELISA revealed 4.6% antigen positivity, indicating infection with viable cysticerci. Taenia eggs were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Alto Benfica, 3.6%), may be explained by sociodemographic factors, which should be analysed in future studies. Previous studies from Mozambique found in general higher prevalence of either antigens (15%) or antibodies (10%) to T. solium larva than the ones reported in this study [14,15], and were consistent with studies done in other settings such as Cameroon [27], Nigeria [28], Vietnam [29,30], Zambia [31] and Democratic Republic of Congo [5], which reported similar seroprevalence rates. In our study, only 12.5% of the screened sera tested simultaneously positive to both serological assays.…”
Section: Serologysupporting
confidence: 92%
See 2 more Smart Citations
“…Alto Benfica, 3.6%), may be explained by sociodemographic factors, which should be analysed in future studies. Previous studies from Mozambique found in general higher prevalence of either antigens (15%) or antibodies (10%) to T. solium larva than the ones reported in this study [14,15], and were consistent with studies done in other settings such as Cameroon [27], Nigeria [28], Vietnam [29,30], Zambia [31] and Democratic Republic of Congo [5], which reported similar seroprevalence rates. In our study, only 12.5% of the screened sera tested simultaneously positive to both serological assays.…”
Section: Serologysupporting
confidence: 92%
“…To the contrary, in Tanzania [43], females were more likely to be seropositive, while in Burkina Faso and Vietnam this was true for males [29,58]. On the other hand, neither gender nor age presented a statistically significant association with seropositivity to cysticercosis in other studies [30,44,46,60].…”
Section: Risk Factors and Multivariate Logistic Regressionmentioning
confidence: 69%
See 1 more Smart Citation